Recycling method of sodium ferric sulfate in secondary battery, sodium ferric sulfate composite material, positive plate and sodium ion battery

CN119361877APending Publication Date: 2025-01-24JIANGSU ZOOLNASM ENERGY TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411209912.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

When the prior art recovers sodium ferric sulfate in sodium ion batteries, high-temperature sintering consumes energy and complex sectional heat treatment process. Spray drying leads to reduced material purity and complex process, making it difficult to achieve large-scale recycling.

Method used

By mixing the positive pole tablets of the secondary battery with the removal water, the solution with sodium sulfate -containing sodium sulfate is obtained, and the sodium sulfate is used to crystallize the sodium sulfate. Composite materials.

Benefits of technology

The recovery purity and electrochemical performance of sodium iron sulfate are improved, the process flow is simplified, energy consumption is reduced, and large-scale recycling of sodium iron sulfate in secondary batteries is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361877A_ABST
    Figure CN119361877A_ABST
Patent Text Reader

Abstract

The invention provides a recovery treatment method of sodium ferric sulfate in a secondary battery, a sodium ferric sulfate composite material, a positive plate and a sodium ion battery. A positive active material in the positive plate of the secondary battery contains a sodium ferric sulfate material; the recycling treatment method comprises the following steps: mixing a positive pole piece disassembled from the secondary battery with deionized water, and crushing to prepare a first mixture; carrying out solid-liquid separation on the first mixture to obtain a solution containing sodium ferric sulfate; mixing the solution containing the sodium ferric sulfate with an alcohol solvent, and crystallizing and separating out the sodium ferric sulfate to obtain a precipitate, so as to obtain a sodium ferric sulfate reclaimed material; and carrying out ball milling on a second mixture containing the recycled ferric sodium sulfate material and a conductive agent, and then carrying out heat treatment to prepare the ferric sodium sulfate composite material. The recycling method provided by the invention can effectively realize large-scale recycling of the sodium ferric sulfate in the secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical technology, and in particular to a method for recovering and treating sodium ferric sulfate in a secondary battery, a sodium ferric sulfate composite material, a positive electrode sheet and a sodium ion battery. Background Art

[0002] In recent years, with the continuous progress of sodium ion battery technology and the improvement of energy density, the demand for sodium ion batteries in the field of new energy vehicles and energy storage power sources has increased significantly. Sodium iron sulfate positive electrode materials have become the first choice for manufacturing sodium ion batteries due to their ultra-long life, fast charging and discharging, low temperature resistance, and safe use. However, with the production and use of sodium ion batteries, the amount of waste sodium ion batteries will gradually increase, and waste sodium ion batteries will accumulate. At present, in order to achieve the recovery of sodium iron sulfate in sodium ion batteries, the traditional recovery method is usually to form a solution containing sodium iron sulfate by high-temperature sintering, segmented heat treatment or spray drying. Among them, the energy consumption of high-temperature sintering is relatively high; the segmented heat treatment process is relatively complicated; and spray drying easily leads to the sodium salt in the positive electrode sheet, the by-products produced during the battery cycle and other impurities and sodium iron sulfate are produced together, which reduces the purity of the obtained sodium iron sulfate material. At the same time, spray drying requires the introduction of additional equipment such as spray drying, and the process is relatively complicated, which is not conducive to the large-scale recovery and utilization of sodium iron sulfate in secondary batteries. Summary of the invention

[0003] Based on this, the present application provides a method for recycling sodium ferric sulfate in a secondary battery, a sodium ferric sulfate composite material, a positive electrode sheet and a sodium ion battery, which can effectively realize the large-scale recycling of sodium ferric sulfate in secondary batteries.

[0004] The first aspect of the present application provides a method for recovering sodium iron sulfate in a secondary battery, wherein the positive electrode active material in the positive electrode sheet of the secondary battery contains a sodium iron sulfate material, comprising:

[0005] The positive electrode sheet disassembled from the secondary battery is mixed with deionized water and then crushed to prepare a first mixture;

[0006] Performing solid-liquid separation on the first mixture to obtain a solution containing sodium ferric sulfate;

[0007] The sodium ferric sulfate-containing solution is mixed with an alcohol solvent to crystallize the sodium ferric sulfate into a precipitate, thereby obtaining a sodium ferric sulfate recovery material;

[0008] The second mixture including the sodium ferric sulfate recycled material and the conductive agent is ball-milled and then heat-treated to prepare a sodium ferric sulfate composite material.

[0009] In some embodiments of the present application, one or more of the following conditions are met:

[0010] (1) The mass ratio of the positive electrode sheet to the deionized water is 1:(5-10), and can be optionally 1:(6-8);

[0011] (2) The temperature of the deionized water is 20°C to 60°C;

[0012] (3) The pulverization time is 1h~5h.

[0013] In some embodiments of the present application, the mass ratio of the alcohol solvent to the deionized water is 1:(0.5~1.2), and can be optionally 1:(0.5~1).

[0014] In some embodiments of the present application, the alcohol solvent includes one or more of ethanol, methanol and isopropanol.

[0015] In some embodiments of the present application, one or more of the following conditions are met:

[0016] (1) The mass proportion of the conductive agent in the second mixture is 2% to 10%, and can be 5% to 10%;

[0017] (2) The conductive agent includes conductive carbon;

[0018] Optionally, the conductive carbon includes one or more of carbon nanotubes, graphene, carbon fiber and graphite.

[0019] In some embodiments of the present application, the ball milling satisfies one or more of the following conditions:

[0020] (1) The ball-to-material ratio of the ball mill is (10-15):1;

[0021] (2) The ball milling time is 2h~6h.

[0022] In some embodiments of the present application, the heat treatment satisfies one or more of the following conditions:

[0023] (1) The temperature of the heat treatment is 120°C to 180°C;

[0024] (2) The heat treatment time is 10h~12h.

[0025] The second aspect of the present application provides a sodium iron sulfate composite material, which is prepared by the recycling method described in the first aspect of the present application.

[0026] The third aspect of the present application provides a positive electrode sheet comprising the sodium iron sulfate composite material described in the second aspect of the present application.

[0027] The fourth aspect of the present application provides a sodium ion battery, comprising the positive electrode sheet described in the third aspect of the present application.

[0028] The fifth aspect of the present application provides an electronic device, comprising the sodium ion battery described in the fourth aspect of the present application.

[0029] The electronic device of the present application includes the sodium ion battery provided by the present application, and thus has at least the same advantages as the sodium ion battery.

[0030] The recovery and treatment method provided by the present application uses an alcohol solvent to precipitate sodium ferric sulfate from a solution containing sodium ferric sulfate in a crystallized form, and extracts the sodium ferric sulfate; at the same time, the positive electrode sheet disassembled from the secondary battery, and the solution containing sodium ferric sulfate prepared by using it will have residual electrolyte solvents, sodium salts, and impurities such as by-products generated during the use and circulation of the secondary battery. While the sodium ferric sulfate is precipitated in a crystallized form by using an alcohol solvent, the above impurities can still remain in the solution, thereby reducing the impurities carried on the surface of the prepared sodium ferric sulfate, and greatly improving the purity of the sodium ferric sulfate extracted from the solution. Therefore, the sodium ferric sulfate recovered material obtained by the recovery and treatment method provided by the present application has a higher purity, and thus has better electrochemical properties; the sodium ferric sulfate composite material obtained after the obtained sodium ferric sulfate recovered material is treated with a conductive agent also has good electrochemical properties. At the same time, the recycling method of the present application, when recovering sodium ferric sulfate, only needs to add an alcohol solvent to the solution containing sodium ferric sulfate, without introducing additional equipment such as spray drying. The process is simple, energy consumption is reduced, and costs are reduced, and it is easy to achieve large-scale recycling of sodium ferric sulfate in secondary batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] FIG. 1 is an X-ray diffraction diagram of the sodium iron sulfate composite material prepared in Example 1. DETAILED DESCRIPTION

[0032] In order to facilitate understanding of the present application, the present application will be described more comprehensively below. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.

[0033] For simplicity, this application only explicitly discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an unclearly recorded range; and any lower limit can be combined with other lower limits to form an unclearly recorded range, and any upper limit can be combined with any other upper limit to form an unclearly recorded range. In addition, although not clearly recorded, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unclearly recorded range.

[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are for the purpose of describing specific embodiments only and are not intended to limit this application. It should be noted that, unless otherwise specified, the term "and / or" used herein includes any and all combinations of one or more related listed items, and "above" and "below" are inclusive of the number, and the meaning of "multiple" in "one or more" is more than two.

[0035] Herein, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values ​​within the numerical interval is considered to be continuous and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when a numerical interval only refers to integers within the numerical interval, including the two endpoint integers of the numerical range, and each integer between the two endpoints, is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be combined. In other words, unless otherwise specified, the numerical ranges disclosed herein should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows broadly including numerical interval types such as percentage intervals, ratio intervals, and ratio intervals.

[0036] In this article, if there are multiple steps involved in the method flow, unless there is a clear different description in this article, there is no strict order restriction for the execution of these steps, and they can be executed in other orders than described. Moreover, any step can include multiple sub-steps or multiple stages, and these sub-steps or stages are not necessarily executed at the same time, but can be executed at different times, and their execution order is not necessarily sequential, but can be executed in turn, alternating or simultaneously with other steps or parts of sub-steps or stages of other steps.

[0037] The above application content of the present application is not intended to describe each disclosed embodiment or each implementation in the present application. The following description more specifically illustrates exemplary embodiments. In many places throughout the application, guidance is provided by a series of examples, which can be used in various combinations. In each example, enumeration is only used as a representative group and should not be interpreted as exhaustive.

[0038] In a first aspect, the present application provides a method for recovering sodium iron sulfate in a secondary battery, wherein the positive electrode active material in the positive electrode sheet of the secondary battery contains sodium iron sulfate material, which may include the following steps S1 to S4:

[0039] S1, mixing the positive electrode sheet disassembled from the secondary battery with deionized water and then crushing it to prepare a first mixture;

[0040] S2, performing solid-liquid separation on the first mixture to obtain a solution containing sodium ferric sulfate;

[0041] S3, mixing the sodium ferric sulfate-containing solution with an alcohol solvent to crystallize the sodium ferric sulfate into a precipitate, thereby obtaining a sodium ferric sulfate recovery material;

[0042] S4, ball-milling the second mixture containing the sodium ferric sulfate recovered material and the conductive agent and then heat-treating it to prepare a sodium ferric sulfate composite material.

[0043] In the above recovery and treatment method provided in the present application, step S1 mixes the positive electrode plate with deionized water and then performs a crushing treatment, so that the sodium ferric sulfate in the positive electrode plate can be more fully dissolved in the deionized water, thereby achieving full dissolution of the sodium ferric sulfate in the positive electrode plate. Step S2 performs solid-liquid separation on the first mixture to obtain a solution containing sodium ferric sulfate. Step S3 mixes the solution containing sodium ferric sulfate with an alcohol solvent. Since the solubility of sodium ferric sulfate in alcohol solvents is low, as the alcohol solvent is continuously added, the sodium ferric sulfate will gradually crystallize from the solution to form a precipitate, thereby achieving the recovery of sodium ferric sulfate. In step S4, the second mixture including the sodium ferric sulfate recovered material and the conductive agent is ball-milled to allow the conductive agent to be inserted into the sodium ferric sulfate recovered material, thereby improving the conductivity of the recovered material; heat treatment is then performed to dry out the crystal water in the sodium ferric sulfate recovered material and allow the conductive agent to more fully enter the sodium ferric sulfate, thereby improving the stability of the sodium ferric sulfate composite material, so that the prepared sodium ferric sulfate composite material can be used as a positive electrode material and put into subsequent battery cycle applications.

[0044] Therefore, the recovery and treatment method of the present application can extract sodium ferric sulfate from the solution by using an alcohol solvent to precipitate sodium ferric sulfate in a crystallized form. At the same time, impurities such as electrolyte solvents, sodium salts, and byproducts produced during the circulation process that may remain in the solution after the battery is disassembled can still remain in the solution, thereby greatly improving the purity of the sodium ferric sulfate extracted from the solution. Compared with the method of obtaining sodium ferric sulfate by spray drying the solution, the sodium ferric sulfate recovered material obtained by the recovery and treatment method of the present application has a higher purity, and thus has better electrochemical performance; and the recovery and treatment method of the present application, when recovering sodium ferric sulfate, only needs to add an alcohol solvent to the solution containing sodium ferric sulfate, without the need to introduce additional equipment such as spray drying, and the process is simple, and it is easy to realize large-scale recycling of sodium ferric sulfate in secondary batteries.

[0045] In addition, unlike the traditional preparation process of sodium ferric sulfate, which requires the raw materials to be subjected to high-temperature sintering (the high-temperature sintering temperature is usually 300°C~400°C) to obtain sodium ferric sulfate, the present application uses alcohol solvents to crystallize sodium ferric sulfate from the solution when obtaining sodium ferric sulfate; since the precipitated material itself is sodium ferric sulfate, the recovery and preparation of sodium ferric sulfate does not require high-temperature sintering, and it only needs to dry out the moisture in the precipitated material at a low temperature (the temperature may not exceed 200°C), thereby greatly simplifying the process, reducing energy consumption, reducing costs, and facilitating large-scale use.

[0046] In some embodiments, the mass ratio of the positive electrode plate to the deionized water is 1:(5-10). For example, the mass ratio may be 1:5, 1:6, 1:7, 1:8, 1:9, 1:10; or 1:(6-8). In this way, more sodium ferric sulfate can be dissolved in the deionized water, and the sodium ferric sulfate can be fully dissolved, thereby improving the recovery rate of the sodium ferric sulfate.

[0047] In some embodiments, the temperature of the deionized water is 20° C. to 60° C. For example, the temperature of the deionized water may be 20° C., 25° C., 30° C., 35° C., 40° C., 45° C., 50° C., 55° C., 60° C., or any range thereof. This is conducive to promoting the dissolution of sodium ferric sulfate in deionized water, so that more sodium ferric sulfate is dissolved in the deionized water.

[0048] In some embodiments, the pulverization time is 1 hour to 5 hours. For example, the pulverization time can be 1 hour, 2 hours, 3 hours, 4 hours, 5 hours or any range of the above values. In this way, the positive electrode sheet can be pulverized more thoroughly, thereby promoting more sodium iron sulfate to dissolve in deionized water.

[0049] In some embodiments, step S1 can be to place the positive electrode plate and deionized water in a stirrer for high-speed stirring and mixing, and use the shear force of high-speed stirring to crush the positive electrode plate, so that the sodium iron sulfate in the plate is fully dissolved in the deionized water.

[0050] In some embodiments, in step S2, the first mixture may be filtered using a sieve, and the pore size of the sieve may be 0.065 mm to 0.15 mm.

[0051] In some embodiments, the mass ratio of the alcohol solvent to the deionized water is 1:(0.5-1.2). For example, the mass ratio may be 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2 or within the range of any of the above values; 1:(0.5-1) may be selected. In this way, the crystallization of sodium ferric sulfate is promoted, so that it is more completely precipitated from the solution, thereby improving the recovery rate of sodium ferric sulfate.

[0052] In some embodiments, the alcohol solvent includes one or more of ethanol, methanol and isopropanol.

[0053] In some embodiments, in step S3, an alcohol solvent may be gradually added to the solution containing sodium ferric sulfate, and the solution is continuously stirred during the addition process, so that the sodium ferric sulfate gradually crystallizes and precipitates.

[0054] In some embodiments, the ball-to-material ratio of the ball milling is (10-15): 1. For example, the ball-to-material ratio can be 10: 1, 11: 1, 12: 1, 13: 1, 14: 1, 15: 1 or within the range of any of the above values. In this way, it is beneficial to fully ball mill the sodium ferric sulfate recovery material and the conductive agent, so that more conductive agent is inserted into the sodium ferric sulfate, which is beneficial to improve the conductive properties of the sodium ferric sulfate composite material.

[0055] In some embodiments, the ball milling time is 2 hours to 6 hours. For example, the ball milling time can be 2 hours, 3 hours, 4 hours, 5 hours, 6 hours or in the range of any of the above values. In this way, it is beneficial to more fully ball mill the sodium ferric sulfate recovery material and the conductive agent, so that more conductive agent is inserted into the sodium ferric sulfate, which is beneficial to improve the conductive properties of the sodium ferric sulfate composite material.

[0056] It can be understood that the "ball-to-material ratio" mentioned in this application refers to the mass ratio between the total amount of ball-milled material and the ball-milling medium.

[0057] In some embodiments, the ball milling medium is not particularly limited and can be selected according to actual needs. For example, the ball milling medium can be zirconia balls.

[0058] In some embodiments, the ball milling is performed under a protective atmosphere; the protective atmosphere may be, for example, a nitrogen atmosphere.

[0059] In some embodiments, the mass proportion of the conductive agent in the second mixture is 2% to 10%. For example, the mass proportion can be 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or in the range of any of the above values; it can be 5% to 10%. In this way, the obtained sodium iron sulfate composite material can have good conductivity, and the conductive agent can occupy as little sodium iron sulfate as possible, so that the sodium iron sulfate composite material has a higher capacity.

[0060] In some embodiments, the conductive agent includes conductive carbon.

[0061] In some embodiments, the conductive carbon includes one or more of carbon nanotubes, graphene, carbon fibers, and graphite.

[0062] In some embodiments, the temperature of the heat treatment is 120°C to 180°C. For example, the temperature of the heat treatment may be 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C or any range thereof. In this way, the crystal water in the sodium ferric sulfate recovery material can be removed, and the conductive agent can be more fully introduced into the sodium ferric sulfate, thereby effectively improving the stability of the sodium ferric sulfate composite material and reducing energy consumption.

[0063] In some embodiments, the heat treatment time is 10 hours to 12 hours. For example, the heat treatment time can be 10 hours, 11 hours, 12 hours or in the range of any of the above values. In this way, the crystal water in the sodium ferric sulfate recovery material is dried out, and the conductive agent can be more fully introduced into the sodium ferric sulfate, thereby improving the stability of the sodium ferric sulfate composite material.

[0064] In some embodiments, the heat treatment is performed under a protective atmosphere; the protective atmosphere may be, for example, a nitrogen atmosphere.

[0065] In a second aspect, the present application provides a sodium iron sulfate composite material, which is prepared by the recycling method described in the first aspect of the present application.

[0066] In a third aspect, the present application provides a positive electrode sheet comprising the sodium iron sulfate composite material described in the second aspect of the present application.

[0067] In some embodiments, the sodium iron sulfate composite material can be used as a positive electrode material and applied in a positive electrode sheet.

[0068] In a fourth aspect, the present application provides a sodium ion battery, comprising the positive electrode sheet described in the third aspect of the present application.

[0069] In some embodiments, the sodium ion battery further includes a negative electrode sheet, a separator and an electrolyte. During the battery charge and discharge process, sodium ions are inserted and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0070] In a fifth aspect, the present application provides an electronic device comprising the sodium ion battery described in the fourth aspect of the present application.

[0071] In some embodiments, the type of electronic device is not particularly limited, and it can be any electronic device known in the prior art. For example, the electronic device can include, but is not limited to, power tools, electric cars, laptop computers, pen-type computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, etc.

[0072] Example

[0073] The following are specific examples, which more specifically describe the contents disclosed in this application, and these examples are only for illustrative purposes, because it is obvious to those skilled in the art that various modifications and variations are made within the scope of the disclosure of this application. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are based on weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.

[0074] Example 1

[0075] (1) Disassemble the failed sodium iron sulfate battery cell and remove the positive electrode. Put the positive electrode and deionized water in a blender at a mass ratio of 1:6 and stir at high speed to crush the electrode using shear force to accelerate the dissolution of sodium iron sulfate; the stirring time is 3 hours and the water temperature is 40°C.

[0076] (2) The stirred solution was filtered using a sieve with a pore size of 0.1 mm.

[0077] (3) Add ethanol to the solution obtained after filtration, with the mass ratio of ethanol to deionized water in step (1) being 1:1. Stir the solution during the addition process to precipitate a white precipitate, thereby obtaining a sodium ferric sulfate recovery material.

[0078] (4) Take 95 g of the sodium iron sulfate recovery material and 5 g of carbon nanotubes (CNT) precipitated from the crystallization, add 1000 g of zirconia balls, set the ball-to-material ratio to 10:1, fill with nitrogen protection, and perform ball milling. The ball milling speed is 700 r / min, the rotational speed is 350 r / min, and the ball milling time is 4 h.

[0079] (5) The ball-milled material is transferred to a box furnace for heat treatment under a nitrogen protective atmosphere and baked at 180°C for 12 h. The baked product is ground into powder to obtain a sodium iron sulfate composite material.

[0080] Example 2

[0081] The preparation method is similar to that of Example 1, with the main difference being that in step (3), the mass ratio of ethanol to deionized water is 1:0.5.

[0082] Example 3

[0083] The preparation method is similar to that of Example 1, with the main difference being that in step (3), the mass ratio of ethanol to deionized water is 1:0.8.

[0084] Example 4

[0085] The preparation method is similar to that of Example 1, with the main difference being that in step (3), the mass ratio of ethanol to deionized water is 1:1.2.

[0086] Example 5

[0087] The preparation method is similar to that of Example 1, with the main difference being that in step (1), the mass ratio of the positive electrode sheet to deionized water is 1:8.

[0088] Example 6

[0089] The preparation method is similar to that of Example 1, with the main difference being that in step (1), the mass ratio of the positive electrode sheet to deionized water is 1:3.

[0090] Example 7

[0091] The preparation method is similar to that of Example 1, with the main difference being that in step (4), the mass proportion of carbon nanotubes is 2%.

[0092] Example 8

[0093] The preparation method is similar to that of Example 1, with the main difference being that in step (4), the mass proportion of carbon nanotubes is 10%.

[0094] Example 9

[0095] The preparation method is similar to that of Example 1, with the main difference being that in step (5), the heat treatment temperature is 120°C.

[0096] Example 10

[0097] The preparation method is similar to that of Example 1, with the main difference being that in step (3), isopropanol is used instead of the alcohol solvent.

[0098] Comparative Example 1

[0099] The preparation method is similar to that of Example 1, with the main differences being that step (3) is omitted, the solution obtained after filtration in step (2) is spray dried, the inlet temperature is set to 150°C, the outlet temperature is set to 60°C, the feed rate is set to 200 mL / h, and sodium iron sulfate recovery material is obtained; in step (5), the heat treatment temperature is 180°C.

[0100] Comparative Example 2

[0101] The preparation method is similar to that of Example 1, with the main difference being that in step (4), only the sodium iron sulfate recovery material and the carbon nanotubes are mixed, and the ball milling process is omitted.

[0102] Comparative Example 3

[0103] The preparation method is similar to that of Example 1, except that in step (3), tetrahydrofuran (ether solvent) is used instead of ethanol, and the mass ratio of tetrahydrofuran to deionized water in step (1) is 1:1.

[0104] The sodium iron sulfate composite materials prepared in Examples 1 to 10 and Comparative Examples 1 to 3 and the button batteries further prepared therefrom were subjected to relevant performance tests, and the test results are shown in Table 1 below.

[0105] Among them, the test conditions or test standards for each performance test item are as follows:

[0106] (1) XRD test

[0107] The test was carried out using an X-ray diffraction analyzer (model: Japanese Rigaku MiniFlex600 X-ray diffractometer).

[0108] (2) Electrochemical performance test

[0109] Preparation of button cell: 9 g of sodium iron sulfate composite positive electrode material, 0.5 g of Super-p as a conductive agent and 0.5 g of polyvinylidene fluoride as a binder were weighed, dispersed in N-methylpyrrolidone solvent, mixed evenly and coated on carbon-coated aluminum foil, and dried under vacuum at 120 °C for 12 h to obtain a positive electrode sheet with a surface density of 16.6 mg / cm 2The positive electrode sheet, glass fiber separator and metal sodium sheet were assembled in order, and 20 μL of electrolyte was injected to obtain a button battery; the solvent of the electrolyte was PC, and the solute was 1 mol / L sodium perchlorate.

[0110] The button cell was charged to 4.5V at a constant current of 0.1C (C=120mA), left for 10min, and discharged to 2.0V at a constant current of 0.1C to obtain the discharge specific capacity.

[0111] (3) Recovery rate of sodium ferric sulfate

[0112] The recovery rate of sodium ferric sulfate is calculated by calculating the theoretical mass of sodium ferric sulfate based on the mass of the positive electrode obtained after disassembling the failed battery cell. The mass of the sodium ferric sulfate finally recovered, i.e., the mass of the sodium ferric sulfate recovered material obtained in step (3), is compared with the theoretical mass to obtain the recovery rate of sodium ferric sulfate.

[0113] (4) Purity of recovered sodium ferrous sulfate

[0114] The mass ratios of Fe, Ca, Al, K, Mg, Mn and Zn in the sodium ferric sulfate recovery material were measured by inductively coupled plasma (ICP), which were recorded as C Fe , C Ca , C Al , C K , C Mg , C Mn , C Zn , the purity of sodium ferric sulfate recovery material can be expressed as R=C Fe / (C Fe +C Ca +C Al +C K +C Mg +C Mn +C Zn ), the higher the value, the higher the purity.

[0115] Table 1

[0116]

[0117] In Table 1, it can be seen from the comparison of Examples 1 to 10 with Comparative Example 1 that, compared with the spray drying method, the recycling method of the present application can improve the purity of the sodium ferric sulfate recovery material; and when the mass ratio of ethanol to deionized water meets 1:0.5, the recycling method of the present application can also take into account the recovery rate of sodium ferric sulfate. It can be seen from the comparison of Examples 1 to 10 with Comparative Example 2 that ball milling of the sodium ferric sulfate recovery material and the conductive agent can effectively improve the discharge specific capacity. It can be seen from the comparison of Examples 1 to 10 with Comparative Example 3 that the recycling method of the present application uses an alcohol solvent to extract sodium ferric sulfate, which can improve the purity of the sodium ferric sulfate recovery material and the recovery rate of sodium ferric sulfate. Therefore, the recycling method provided by the present application can effectively realize the large-scale recycling of sodium ferric sulfate in secondary batteries. At the same time, it can be seen from Figure 1 that after recycling, Example 1 has obtained sodium ferric sulfate recovery material.

[0118] In addition, when comparing Examples 1 to 4, it can be seen that when the mass ratio of ethanol to deionized water is 1: (0.5 to 1), the discharge specific capacity and the recovery rate of sodium iron sulfate are relatively higher. When comparing Examples 1, 5, and 6, it can be seen that when the mass ratio of the positive electrode sheet to deionized water is 1: (6 to 8), the recovery rate of sodium iron sulfate is relatively higher. When comparing Examples 1, 7, and 8, it can be seen that when the mass proportion of carbon nanotubes is 5% to 10%, the electrochemical performance of the sodium iron sulfate composite material is relatively higher.

[0119] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0120] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.

Claims

1. A method for recovering sodium iron sulfate in a secondary battery, characterized in that: The positive electrode active material in the positive electrode sheet of the secondary battery contains sodium iron sulfate material, including: The positive electrode sheet disassembled from the secondary battery is mixed with deionized water and then crushed to prepare a first mixture; Performing solid-liquid separation on the first mixture to obtain a solution containing sodium ferric sulfate; The sodium ferric sulfate-containing solution is mixed with an alcohol solvent to crystallize the sodium ferric sulfate into a precipitate, thereby obtaining a sodium ferric sulfate recovery material; The second mixture including the sodium ferric sulfate recycled material and the conductive agent is ball-milled and then heat-treated to prepare a sodium ferric sulfate composite material.

2. The recycling method according to claim 1, characterized in that: Meet one or more of the following conditions: (1) The mass ratio of the positive electrode sheet to the deionized water is 1:(5-10), and can be optionally 1:(6-8); (2) The temperature of the deionized water is 20°C to 60°C; (3) The pulverization time is 1h~5h.

3. The recycling method according to claim 1 or 2, characterized in that: The mass ratio of the alcohol solvent to the deionized water is 1:(0.5-1.2), and can be optionally 1:(0.5-1).

4. The recycling method according to claim 3, characterized in that: The alcohol solvent includes one or more of ethanol, methanol and isopropanol.

5. The recycling method according to claim 1 or 2, characterized in that: Meet one or more of the following conditions: (1) The mass proportion of the conductive agent in the second mixture is 2% to 10%, and can be 5% to 10%; (2) The conductive agent includes conductive carbon; Optionally, the conductive carbon includes one or more of carbon nanotubes, graphene, carbon fibers and graphite.

6. The recycling method according to claim 1 or 2, characterized in that: The ball milling satisfies one or more of the following conditions: (1) The ball-to-material ratio of the ball mill is (10-15):1; (2) The ball milling time is 2h~6h.

7. The recycling method according to claim 1 or 2, characterized in that: The heat treatment satisfies one or more of the following conditions: (1) The temperature of the heat treatment is 120°C to 180°C; (2) The heat treatment time is 10h~12h.

8. A sodium iron sulfate composite material, characterized in that: It is prepared by the recovery and treatment method according to any one of claims 1 to 7.

9. A positive electrode sheet, characterized in that: The invention comprises the sodium iron sulfate composite material according to claim 8.

10. A sodium ion battery, characterized in that: Including the positive electrode sheet as described in claim 9.

Citation Information

Cited By

  • Regeneration method and application of invalid sodium ferric sulfate positive electrode material

    CN120978259A

  • Method for regenerating waste ferric sodium sulfate positive electrode material by recycling high-value carbon source and PVDF (polyvinylidene fluoride)

    CN121507184A